A case report and literature review: leiomyosarcoma or perivascular epithelioid cell neoplasm? - Chen, Zheng; Zheng, Xuan; Lin, Qin (Frontiers in Oncology, 2024)
The distinction between a uterine leiomyosarcoma (uLMS) and a perivascular epithelioid cell neoplasm (PEComa) can be quite challenging. Here we report a 39-year-old woman who underwent a hysteroscopic myomectomy. An intraoperative frozen section pathological examination revealed that the mass was likely to be a mesenchymal malignancy. After consultation with her family, a total hysterectomy and bilateral salpingo-oophorectomy were performed. Postoperative pathological examinations suggested leiomyosarcoma but a malignant PEComa cannot be completely excluded. Combining the present case and prior studies, we summarized the clinical manifestations, pathological features, genomic characterization, and treatment of LMS and PEComa.